Bed-sharing and risk of hospitalisation due to pneumonia and diarrhoea in infancy: the 2004 Pelotas Birth Cohort - Ngale, Kátia M A (BMJ Publishing Group, 2013)
OBJECTIVE: To investigate the association between bed-sharing with the mother at 3 months of age and incidence of hospitalisation due to pneumonia and diarrhoea between 3 and 12 months. METHODS: The 2004 Pelotas Birth Cohort included all live births to mothers living in Pelotas, Brazil, in 2004. Information on bed-sharing was obtained at the 3-month follow-up visit, and on hospitalisations at the 12-month visit, both based on mothers’ reports. Only singleton infants with complete information on hospitalisation were analysed. RESULTS: 3906 infants were included. The bed-sharing prevalence at 3 months was 46.4% (95% CI 44.9 to 48.0%). The incidence of pneumonia admissions between 3 and 12 months was 3.6% (95% CI 3.3 to 4.2%) and diarrhoea, 0.9% (95% CI 0.6 to 1.2%). In crude analyses, bed-sharing with the mother was associated with higher incidence of hospitalisation due to both pneumonia and diarrhoea. There was interaction between bed-sharing and duration of breastfeeding regarding the chance of admission due to pneumonia. Among infants breastfed for 3 months or less, the chance of hospitalisation due to pneumonia among bed-sharers was almost twice as high as among non-bed-sharers (adjusted OR 1.96; 95% CI 1.08 to 3.55). There was no association between bed-sharing and hospitalisation due to pneumonia among infants breastfed for longer than 3 months in crude or adjusted analyses. The association between bed-sharing and admissions due to diarrhoea lost statistical significance after allowing for confounders. CONCLUSIONS: The effect of bed-sharing in infancy on the risk of hospitalisation due to pneumonia depends on breastfeeding, such that weaned children present higher risk.